Digestibility of rumen undegradable protein from 40 browse species measured by mobile nylon bag and in vitro techniques - Kaitho, R.J.; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S.; Bruchem, J. van (Cambridge University Press, 1998)
Crude protein concentration and energy value of cereal crop residues and poor quality grasses are below animal requirements during much of the year and browses have been incorporated in the feeding systems to improve the nutritional status of ruminants. Leaves and fruits of leguminous browses can be used as protein supplements for ruminants and are commonly used as foods in many agricultural systems. The new systems of protein evaluation (Agricultural and Food Research Council, 1992; Tamminga et al., 1994) partition food nitrogen into the amount degraded in the rumen and that which escapes ruminal degradation. Protein available for absorption post-ruminally is influenced by the amount of food nitrogen that is resistant to ruminal degradation plus microbial protein (Brown and Pitman, 1991). Several studies have been carried out to assess the digestibility of ruminal escape protein (Hvelplund, 1985; Frydrych, 1992), and the digestibility varies considerably across foods (Krishnamoorthy et al., 1982). Values between 0·80 and 0·85 are adopted for the true digestibility of protein from temperate foods and from microbial amino acids (van Bruchem et ah, 1989). However, no data are available on intestinal digestibility of browses although they have been recognized as good protein supplements. The mobile nylon bag (MNB) method is useful for assessing the digestibility of rumen undegradable food protein in the intestine (de Boer et ah, 1987). Since the MNB is labourious, it was desirable to assess the accuracy with which an in vitro (pepsin/pancreatin) procedure could predict results from the former. Therefore, the objective of this study was to determine apparent digestibility of browse rumen undegradable protein using MNB method and pepsin/pancreatin in vitro technique.